IN SILICO CHARACTERIZATION OF NITRATE REDUCTASE INVOLVED IN GOLD NANOPARTICLES SYNTHESIS IN PSEUDOMONAS DENITRIFICANS - RASHMI GUPTA,; KOEL MUKHERJEE,; SNEHA SINGH, (International Journal of Pharma and Bio Sciences, 2014)
Various studies suggest the involvement of nitrate reductase in gold nanoparticle synthesis from different bacterial sources. The present study focuses on the in silico characterization of four subunits namely alpha, beta, gamma and delta of respiratory nitrate reductase enzyme using online tools and softwares in Pseudomonas denitrificans .CodonW and CAIcal server are used to perform codon usage biasness study on the respiratory nitrate reductase genes of P. denitrificans. Further different parameters of the physicochemical characterization were analysed by CLC Protein workbench, Expasy ProtParam, BLAST and COBALT. The analysis of various above parameters shows that the expression of gamma subunit is more out of all four subunits, hence suggesting the major involvement of it in gold nanoparticle synthesis. This may help in future to find out ways to enhance gold nanoparticle production in P. denitrificans and other related organisms.